Impact of Patient Compliance on Tooth Loss during Supportive Periodontal Therapy: A Systematic Review and Meta-analysis. (June 2015) - Lee, C.T.; Huang, H.Y.; Sun, T.C.; Karimbux, N.
Periodontal treatment consists of active periodontal therapy (APT) and supportive periodontal therapy (SPT). Regular SPT is recommended to prevent and control the occurrence of periodontal disease following APT. A patient's compliance with SPT is considered one of the most important factors affecting long-term periodontal status. Tooth loss is generally considered the final outcome of periodontitis. This review aimed to analyze the relationship between patient compliance with regular SPT and tooth loss. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guideline for systematic reviews was used. A search of articles was conducted using MEDLINE (PubMed) and other databases. Quality assessments of selected studies were performed. To assess the effect of compliance on tooth loss during SPT, pooled risk ratio of tooth loss (RRTL) was used as the primary outcome. Pooled risk difference of tooth loss (RDTL) and weighted mean difference of tooth loss rate (WDTLR) were used as secondary outcomes. Subgroup analysis and meta-regression were conducted to evaluate the effects of different variables. In total, 710 articles were screened. Eight studies, which had a regular-compliance (RC) group and an erratic-compliance (EC) group with at least a 5-y follow-up period, qualified for the meta-analysis. The risk of tooth loss in the RC group was significantly lower than that in the EC group (pooled RRTL: 0.56 [confidence interval (CI): 0.38, 0.82]; pooled RDTL: –0.05 [CI: –0.08, –0.01]). The definition of compliance was a variable significantly related to risk ratio of tooth loss. Patients in the RC group had significantly lower tooth loss rate during SPT than did patients in the EC group (WDTLR: –0.12 [CI: –0.19, –0.05]). Teeth have less risk of being lost if patients are more compliant with supportive periodontal therapy. However, unidentified variables causing data heterogeneity and affecting the risk of tooth loss may have been present. More well-controlled prospective studies are needed in the future.